Research on the factors affecting the compressive strength of rubber powder modified cement-stabilized crushed stone based on orthogonal experiments - Xu, Feng; Zhu, Xuanxuan; Gao, Qiju (Frontiers in Mechanical Engineering, 2024)
Based on an orthogonal experimental design, this study introduces rubber powder particle size alongside rubber powder content, aggregate gradation, and cement content as factors. A total of 16 mix proportions were formulated. For each mixture, compaction tests and unconfined compressive strength (UCS) tests were conducted. Using Statistical Product and Service Solutions (SPSS) software, a multifactor variance analysis was performed to determine the influence levels of the four factors on maximum dry density and compressive strength. The optimal mix proportion was selected based on compressive strength. The results indicate that aggregate gradation and rubber powder content significantly affect the maximum dry density of the mixture, with aggregate gradation having the greatest impact. Rubber powder content has the most substantial effect on compressive strength, while rubber particle size has the least influence. The optimal formulation is 7% cement content, 30-mesh rubber powder, 0.5% rubber powder content, and a skeletal dense gradation close to the median.